Reply to comment 'On large-N expansion' - Mustafa, O (Iop Publishing Ltd, 2002)
Fernandez comments [1] on our pseudo-perturbative shifted-l expansion technique [2, 3] is either unfounded or ambiguous.
Keywords: Truncated Coulomb Potentials; Bound-States